Swear words on the Instagram account @playitsafebabyreborn - Koebanu, Sabri; Cahyani, Dhiya Turfa Pesona (PT. Hafasy Dwi Nawasena, 2023)
Today's swear words or expressions are increasingly found, especially on social one of them is swearing expressions on the social media account Instagram @playitsafebabyreborn. Many netizens comment as they please without attaching importance to proper grammar and what can be caused by the words thrown at the victim. This study aims to describe any swear expressions obtained and analyze them by mentioning one by one the forms of swear words on the Instagram account @playitsafebabyreborn, including the data in the form of screenshots. This study uses a descriptive research method because this research describes swearing words found on the @playitsafebabyreborn account. Furthermore, this research approach is qualitative because the data is qualitative, namely the comments of netizens in the @playitsafebabyreborn Instagram comment column which contain swear words. The data collection technique used is the free-involvement listening technique because the data collection is done without involving Instagram users or netizens who comment on the Instagram account @playitsafebabyreborn but only observe from Instagram. The data analysis method used is the equivalent method with the determinant element sorting technique. Furthermore, the distribution method is used with the direct element division technique. From the results of this study, there are 15 swear words originating from the comments column and the Instagram account @playitsafebabyreborn. Based on this research, swear expressions can be found in several forms, namely animal lexical, profession lexical, object lexical, state or mental lexical, creature lexical, and epithet lexical.